Exploring psychological dimensions of augmented reality in education: a study on learning motivation and achievement in museums - Anping Cheng; Weiru Zhang; Anran Feng; Yunmengru Wu; Wanjun Li (Frontiers in Psychology)
Augmented reality (AR) has gained significant attention and is being increasingly utilized to enrich the learning experience of museum visitors. This study explores the psychological dimensions of AR in education, focusing on learning motivation and academic achievement in museums. A quantitative research study was carried out, encompassing a survey of 266 visitors at the Wuhan Natural History Museum. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed as the analytical tool to validate the proposed model. The findings reveal significant positive effects of information quality on immersion, imagination, and academic achievement, as well as positive effects of information richness on academic achievement. Information quality mediates the relationship between information richness and immersion/imagination, while immersion and imagination mediate the association between information quality and learning motivation. Additionally, learning motivation positively influences academic achievement. Furthermore, wearable comfort moderates the effect of information quality on immersion and imagination. The study provides theoretical insights into the complex interplay between these variables and their impact on learning motivation and academic achievement. The findings have implications for the design of AR-based learning systems and highlight the importance of considering wearable comfort in enhancing user experiences.